في ماليزيا: دراسة تحليلية تطبيقية (GLC) الزكاة على الشركات المرتبطة بالحكومة - Mohd Effandi, Muhammad Lutfil Hadi; Mat Jubri Shamsuddin, Mustafa (Jurnal Fiqh, 2024)
This paper explores the obligation of zakat on Government Linked Companies (GLCs), highlighting a disparity where most zakat is collected from salaries despite business taxes constituting over half of Malaysia’s tax revenue. The study aims to identify the shariah ruling concerning zakat on GLCs, by examining the requirements for zakat on both the payer and the wealth. It includes an analysis of Malaysian laws and fatwas related to zakat on GLCs, assessing the current applications and the feasibility of enforcing it on these entities. The study finds that al-fuqaha’ disagree on the obligation of governments to pay zakat on investment funds, with a majority deeming them exempt, while a minority advocate for their zakat obligation. The dispute arises from varying interpretations of zakat eligibility for certain types of governments’ wealth. Despite this, several Malaysian states have issued fatwas that seems to support the minority view. However, the enforcement of these rulings may be unconstitutional, due to some misalignments between state authority over zakat and federal authority over corporations